Perawatan Satu Kunjungan Restorasi Pasak Fiber Reinforced Composite Pada Gigi Insisivus Atas - Ria Ariani; Wignyo Hadriyanto (Faculty of Dentistry, Universitas Gadjah Mada, 2013)
Perawatan saluran akar satu kali kunjungan memberikan keuntungan antara lain memperkecil resiko kontaminasi mikroorganisme dan menghemat waktu perawatan. Pasak fiber reinforced composite memiliki ikatan yang baik dengan dentin menggunakan semen resin dan inti dari resin. Penggunaan pasak bisa mengurangi risiko fraktur. Tujuan penulisan laporan kasus ini adalah untuk mengevaluasi hasil restorasi gigi 11 nekrosis pulpa pasca perawatan saluran akar disertai restorasi dengan pasak fiber reinforced composite. Pasien wanita, 22 tahun datang ke Klinik Konservasi RSGM FKG UGM untuk merawat gigi depan atas kanan yang berlubang. Berdasarkan pemeriksaan subjektif, objektif dan radiografis diperoleh diagnosis gigi 11 nekrosis pulpa. pasca perawatan saluran akar gigi Gigi direstorasi dengan resin komposit dan pasak fiber reinforced composite. Kesimpula dari hasil evaluasi klinis saat kontrol tidak ada keluhan rasa sakit dan pasien merasa puas.One Visit Treatment of Fiber Reinforced Compositerestoration in Maxillary Right First Incisivus. One visit root canal treatment is advantageous to minimize the risk of microorganism contamination. It saves time and more tolerable for the patients. Fiber reinforced composite post is fabricated, and it has been known to have a good bond with dentinal wall of root space, resin cement and composite resin core. The use of this post could decrease the risk of fracture. The purpose of this paper is to report the results of dental restoration 11 pulp necrosis after root canal treatment with resin composite restorations and post fiber reinforced composite. A 22 year-old female patient who came to Faculty of Dentistry UGM complained about her maxillary right incisor teeth which decayed and needed a treatment. Based on the subjective, objective and radiograph examinations, it was diagnosed that the pulp was necrotic. After one visit root canal treatment and based on clinical evaluation, it is concluded that the right upper incisor that was restored using fiber reinforced composite post and composite resin showed no pain, and patient was satisfied.